2005
DOI: 10.1172/jci200523273
|View full text |Cite
|
Sign up to set email alerts
|

Role of osteopontin in amplification and perpetuation of rheumatoid synovitis

Abstract: Osteopontin (OPN) is an extracellular matrix protein of pleiotropic properties and has been recently recognized as a potential inflammatory cytokine. In this study, we demonstrate, for the first time to our knowledge, that overexpression of OPN in synovial T cells is associated with local inflammatory milieu and that OPN acts as an important mediator in amplification and perpetuation of rheumatoid synovitis. The study revealed that mRNA expression of OPN was highly elevated in CD4 + synovial T cells derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Analogous to macrophages of adipose tissue in obesity and synovial T cells in rheumatoid synovitis, the overexpression of OPN in psoriasis seems to be correlated to disease severity only in the skin, as suggested by previous studies. The confined reduction of local OPN after systemic therapies or phototherapy may reflect an indirect rather than direct effect of the therapy on OPN levels, once OPN is not proportionally reduced with the decrease of PASI score [28,37,44]. Since OPN plasma levels were also reduced after therapy with adalimumab or etanercept [45], further studies addressing OPN levels in non-responder patients treated with anti-TNF-a are necessary to investigate its importance as an alternative inflammatory pathway in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to macrophages of adipose tissue in obesity and synovial T cells in rheumatoid synovitis, the overexpression of OPN in psoriasis seems to be correlated to disease severity only in the skin, as suggested by previous studies. The confined reduction of local OPN after systemic therapies or phototherapy may reflect an indirect rather than direct effect of the therapy on OPN levels, once OPN is not proportionally reduced with the decrease of PASI score [28,37,44]. Since OPN plasma levels were also reduced after therapy with adalimumab or etanercept [45], further studies addressing OPN levels in non-responder patients treated with anti-TNF-a are necessary to investigate its importance as an alternative inflammatory pathway in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using OPN-deficient mouse models and OPN-neutralizing antibodies (Abs) have demonstrated the importance of OPN in the development of several inflammatory diseases, particularly those involving CD4 T helper 1 (Th1)-associated immune responses [2][3][4][5][6][7][8][9][10]. In humans, high levels of OPN have been observed in several diseases associated with Th1 responses, such as sarcoidosis [11], tuberculosis [11], rheumatoid arthritis [12], Crohn's disease [13], and multiple sclerosis (MS) [14]. However, the role of OPN in Th2-associated diseases, rather than diseases involving Th-1, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The OPN molecule contains a classical cell-binding domain of arginine, glycine, and aspartic acid (RGD) recognized by integrins such as ␣ v ␤ 3 and ␣ 5 ␤ 1 , and an additional cell-binding domain (serine, valine, valine, tyrosine, glycine, lysine, and arginine [SVVYGLR] in humans and serine, lysine, alanine, tyrosine, glycine, lysine, and arginine [SLAYGLR] in mice) that is recognized by ␣ 4 ␤ 1 and ␣ 9 ␤ 1 (Denhardt and Guo, 1993;Yokosaki et al, 1999). OPN has been implicated in the pathogenesis of various intractable inflammatory diseases including rheumatoid arthritis (RA), multiple sclerosis (MS), inflammatory bowel disease, atherosclerosis, inflammatory ocular disease, and allergic airway disease (Chabas et al, 2001;Bruemmer et al, 2003;Matsui et al, 2003;Yamamoto et al, 2003;Diao et al, 2004;Sato et al, 2005;Xu et al, 2005;Hur et al, 2007;Kitamura et al, 2007;Xanthou et al, 2007). Importantly, each of these disorders is associated with high tissue and plasma OPN expression.…”
Section: Introductionmentioning
confidence: 99%